THE RELEVANCE OF ODD-EVEN VERSES IN THE QUR'AN WITH MATHEMATICS EDUCATION - Surur, Agus Miftakus; Pujilestari, Sri (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
Education is an effort to improve knowledge, one of which is by conducting studies on the Qur'an and Mathematics. This research examines the verses of the Qur'an containing odd-even concepts and their relevance to mathematics. By using the library research method, the verse selection step is taken from observations of the translated Qur'an. The mathematical concepts found are materials related to odd-even concepts, such as KPK (Least Common Multiple) and FPB (Greatest Common Factor), Venn diagrams, and Phi in á¹awwÄf. As the result, the number of verses and the number of surahs show odd-even numbers. If the numbers are added up to 38, these will be equal to the number of letters in the syahÄdah sentence.